Secondary metabolites from the stem barks of Rhizophora mucronata Lamk - Linh, Kieu Thi Phuong; Quan, Nguyen Huu; Chien, Nguyen Van; Trung, Nguyen Quoc; Thong, Vu Huy; Tuyen, Nguyen Van; Thao, Nguyen Phuong (Vietnam Journal of Science and Technology, 2020)
Using various chromatographic separations, three phenolic derivatives (1‒3) and three phytosteryl glycosides (4‒6) were isolated from a methanolic extract of R. mucronata stem barks. Their structures were elucidated to be cinchonain Ia (1), breynioside B (2), polystachyol (3), β-sitosterol 3-O-β-D-glucopyranoside (4), β-sitosterol 3-O-β-D-(6’-O-palmitoyl) glucopyran-oside (5), and β-sitosterol 3-O-β-D-(6’-O-stearoyl)glucopyranoside (6) by detailed analysis via spectroscopic techniques (1D, 2D NMR, and ESI-MS data) as well as comparison with those reported. This is the first report of compounds 1‒6 from the Rhizophora genus.